Generalized 2-absorbing and strongly generalized 2-absorbing second submodules - ‎Ansari-Toroghy, H.; Farshadifar, F.; ‎Maleki-Roudposhti, S. (Algebra and Discrete Mathematics, 2020)
In this paper, we will introduce the concepts of generalized 2-absorbing and strongly generalized 2-absorbing second submodules of modules over a commutative ring and obtain some related results.